Two-photon (2P) Microscopy to Study Ca2+ Signaling in Astrocytes From Acute Brain Slices - Annamaria Lia; Micaela Zonta (Bio-Protocol)
Since the discovery that astrocytes are characterized by Ca2+-based excitability, investigating the function of these glial cells within the brain requires Ca2+ imaging approaches. The technical evolution from chemical fluorescent Ca2+ probes with low cellular specificity to genetically encoded indicators (GECIs) has enabled detailed analysis of the spatial and temporal features of intracellular Ca2+ signal. Different imaging methodologies allow the extraction of distinct information on calcium signals in astrocytes from brain slices, with resolution ranging from cell populations to single cells up to subcellular domains.Here, we describe 2-photon laser scanning microscopy (2PLSM) Ca2+ imaging in astrocytes from the somatosensory cortex (SSCx) of adult mice in ex vivo acute cortical slices, performed using two genetically encoded Ca2+ indicators, i.e., cytosolic GCaMP6f and endoplasmic reticulum-targeted G-CEPIA1er. The main advantage of the 2PLSM technique, compared to single-photon microscopy, is the possibility to go deeper in the tissue while avoiding photodamage, by limiting laser excitation to a single focal plane. The fluorescent signal of the indicator is analyzed offline in different compartments—soma, proximal processes, and microdomains—for GCaMP6f experiments and in the perinuclear, somatic area for G-CEPIA1er. The analysis of Ca2+ signal from different compartments, although not providing a value of absolute concentration, allows a critical comparison of the degree of astrocyte activation between different experimental conditions or mouse models. Moreover, the analysis of G-CEPIA1er signal, which reveals metabotropic receptor activation as a dynamic decrease in free Ca2+ in the endoplasmic reticulum (ER), can provide information on possible alterations in this critical second messenger pathway in astrocytes, including, for example, steady-state ER Ca2+ levels and kinetics of Ca2+ release.